Factors influencing the intention to use Grab services in Malaysia / Nur Syafatin Abdullah - Abdullah, Nur Syafatin (Faculty of Business and Management, 2019)
Grab has become the major player in the Malaysian e-hailing industry and people are looking for alternatives to Grab because they want a cheaper option. However, with the growing presence of Grab in Malaysia, fares will continue to be lower and competition will rise, making it impossible for taxi drivers to survive. Therefore, this study seeks to examine factors influencing the intention to use Grab services in Malaysia. The dependent variable in this study was the intention to use Grab services in Malaysia while the independent variables were made up of four variables, namely attitude towards behaviour, subjective norm, perceived behavioural control and perceived ease of use. A total of 200 respondents in Johor Bahru were chosen for this study through a survey questionnaire using convenience sampling method. The Statistical Package for Social Sciences Software (SPSS) was used to key in and analyse all the data obtained. The data was collected in order to make descriptive, correlation and multiple regression analysis. A multiple regression analysis was used to test the relationship among the variables. The result indicates that attitude, perceived behavioural control and perceived ease of use have significant relationship with the intention to use Grab services. The most significant predictor variable of the intention to use Grab services is perceived behavioural control which found that the higher the individual’s perceived behavioural control, the higher the intention to use Grab services. The findings of this study can be very helpful and useful to various parties such as consumers, Grab drivers, businesses as well as government by making Grab services to be more effective and competitive in Malaysia context.